2017
DOI: 10.1140/epjc/s10052-017-5426-0
|View full text |Cite
|
Sign up to set email alerts
|

Black string in dRGT massive gravity

Abstract: We present a cylindrically symmetric solution, both charged and uncharged, which is known as a black string solution to the nonlinear ghost-free massive gravity found by de Rham, Gabadadze, and Tolley (dRGT). This "dRGT black string" can be thought of as a generalization of the black string solution found by Lemos. Moreover, the dRGT black string solution includes other classes of black string solution such as the monopole-black string ones since the graviton mass contributes to the global monopole term as wel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 65 publications
1
37
0
Order By: Relevance
“…Black hole solutions and their thermodynamical properties have been analyzed in dRGT massive gravity [37][38][39][40]. Katsuragawa et al [41] devised a neutron star model that demonstrated that massive gravity dynamics deviates only slightly from GR.…”
Section: Introductionmentioning
confidence: 99%
“…Black hole solutions and their thermodynamical properties have been analyzed in dRGT massive gravity [37][38][39][40]. Katsuragawa et al [41] devised a neutron star model that demonstrated that massive gravity dynamics deviates only slightly from GR.…”
Section: Introductionmentioning
confidence: 99%
“…In the negative Λ case, the black string only has one event horizon. In a generic set-up where the ǫ term in the metric (13) is nonzero, the number of horizon structure in negative Λ case will be different from ours [17].…”
Section: Discussionmentioning
confidence: 68%
“…However, this is not the case for neutral black string with positive Λ. Without the charge term, the metric (13) cannot develop a naked singularity or extremal scenario (for charged black string [17], naked singularity can exist just like in the black hole case). Note that throughout this work, ǫ will be fixed to zero [19].…”
Section: B Static Solutionsmentioning
confidence: 98%
See 2 more Smart Citations